ST-Segment Elevation Myocardial Infarction from Septic Emboli Secondary to Infective Endocarditis by Abiotrophia Defectiva - Bashar Khiatah; Sam Jazayeri; John Wilde; Mathew Westfall; Thomas Q. Kong; Amanda Frugoli (Case Reports in Cardiology)
This article showcases a young patient who presented with STEMI secondary to septic emboli due to endocarditis with Abiotrophia Defectiva in the setting of a congenital bicuspid aortic valve. We aim to discuss current considerations for STEMI in young individuals including embolism due to IE, especially in patients with known or suspected congenital heart valve disease.